Effect of Lemon Scent on Anxiety in Patients before Rhinoplasty Surgery: A Randomized Controlled Trial - Maryam Amirshekari; Mohammad Javad Tarahi; Ahmad Ghadami (Tehran University of Medical Sciences, 2023)
Among cosmetic surgeries, nose surgery is more anxiety-provoking than other surgeries. By causing mental stress, surgery leads to the disruption of vital signs. By releasing endorphins in the brain, aromatherapy leads to a feeling of well-being. This study was conducted to determine "the effect of lemon scent on patients' anxiety before rhinoplasty surgery in Ayatollah Kashani Hospital, Isfahan". This clinical trial was conducted on 30 candidates for rhinoplasty surgery at Kashani Hospital of Isfahan in 2011. Patients were divided into two intervention and control groups (15 people in each group) by random allocation method. The research tool was Spielberger's standard questionnaire, completed immediately before and 20 to 30 minutes after the intervention by two groups. Data were analyzed using SPSS 16 software, descriptive statistics and independent t, paired t and MANCOVA tests at a significance level of less than 0.05. Two groups were homogeneous in terms of demographic variables. The mean latent anxiety score in the intervention group before the intervention (10.06) was 42.26, and after the intervention (8.86) was 35.8, which difference was statistically significant (P = 0.002). The mean overt anxiety score in the intervention group before the intervention (8.66) was 42.60. After the intervention (5.81) was 31.86, this difference was statistically significant (p < 0.001). The results showed a statistically significant difference between the intervention and control groups in the mean of hidden (p = 0.029) and overt anxiety (p = 0.001). Using lemon scent as an effective, non-invasive and cost-effective non-medicinal intervention reduces the preoperative anxiety of rhinoplasty candidates, so it is possible to benefit from the scent of lemon to reduce patients' anxiety.